2020
DOI: 10.1002/anie.202013912
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Capacity and Rate Performance of Transition‐Metal Coordination Compounds for Reversible Lithium Storage

Abstract: Coordination compounds are well‐known compounds that are being used as new materials for lithium storage because of their unique advantages, that is, designable structures, abundant active sites, and facile as well as mild synthetic routes. However, the electrode stability, low rate performance, and cycle life of coordination compounds are currently the main issues preventing their application as electrode materials, and the lithium‐storage mechanism in coordination networks is not well understood. Herein, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Therefore, developing a facile and scalable approach to precisely regulate the anode/ electrolyte interface and suppress side reaction toward stabilized Zn anode is a critical necessity.Coordination compounds, formed by metal centers and organic ligands via coordination bonds, have been applied in numerous fields due to their well-defined compositions and variable structures, abundant active sites, rich functional groups, as well as mild synthetic routes. [18,19] It is worth mentioning that coordination compounds with rich functional groups and ordered open channels exhibits strong affinity for metal ion as well as enable fast and uniform ion flux. [20,21] In addition, coordination bonds can effectively buffer the volume change during charge-discharge processes.…”
mentioning
confidence: 99%
“…Therefore, developing a facile and scalable approach to precisely regulate the anode/ electrolyte interface and suppress side reaction toward stabilized Zn anode is a critical necessity.Coordination compounds, formed by metal centers and organic ligands via coordination bonds, have been applied in numerous fields due to their well-defined compositions and variable structures, abundant active sites, rich functional groups, as well as mild synthetic routes. [18,19] It is worth mentioning that coordination compounds with rich functional groups and ordered open channels exhibits strong affinity for metal ion as well as enable fast and uniform ion flux. [20,21] In addition, coordination bonds can effectively buffer the volume change during charge-discharge processes.…”
mentioning
confidence: 99%
“…Generally, the potential pseudocapacitive behavior of the electrode has been widely regarded as a superior factor for high‐rate capability and enhanced electrochemical kinetics upon continuous cycling process, which can be quantified by the following analysis (The detailed information is supplied in Supporting Information). [ 18 ] The CV scans were first tested at various scan rates from 0.2–1.2 mV s −1 (Figure S22a, Supporting Information). From that we can obtain the b value (Figure S22b, Supporting Information) of ZnV 2 O 4 NFs@N‐PC in different potentials is 0.78, 1.01, 0.93, 0.86, 0.91, and 0.85, respectively, manifesting its fast surface‐dominated capacitive behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the studies on the internal electrochemical mechanism and structural changes being continuously made in this area for further developments. Du et al reported the electrode stability, rate performance, and cycle life for reversible lithium storage of five different one dimensional isostructural MOFs [M(HIPA)(H 2 O) 3 ]n (MHIPAs, M = Mn, Fe, Co, Ni and Zn; H3IPA = 5‐hydroxyisophthalic acid) 39 . The electrode stability based on these five coordination compounds depends upon the metal centre governing the strength of the coordination bonds.…”
Section: Mofs As Anode Materials For Libsmentioning
confidence: 99%
“…Du et al reported the electrode stability, rate performance, and cycle life for reversible lithium storage of five different one dimensional isostructural MOFs [M(HIPA) (H 2 O) 3 ]n (MHIPAs, M = Mn, Fe, Co, Ni and Zn; H3IPA = 5-hydroxyisophthalic acid). 39 The electrode stability based on these five coordination compounds depends upon the metal centre governing the strength of the coordination bonds. The study of lithium storage showed that Co-HIPA and Ni-HIPA can maintain F I G U R E 3 Schematic for metal organic framework (MOFs) synthesis via solvothermal process.…”
Section: Mofs As Anode Materials For Libsmentioning
confidence: 99%